Global Equity Correlation in International Markets - Bae, Joon Woo; Elkamhi, Redouane (Management Science, 2021)
We present empirical evidence that the innovation in global equity correlation is a viable pricing factor in international markets. We develop a stylized model to motivate why this is a reasonable candidate factor and propose a simple way to measure it. We find that our factor has a robust negative price of risk and significantly improves the joint cross-sectional fits across various asset classes, including global equities, commodities, sovereign bonds, foreign exchange rates, and options. In exploring the pricing ability of our factor on the FX market, we also shed light on the link between international equity and currency markets through global equity correlations as an instrument for aggregate risks. This paper was accepted by Karl Diether, finance.